OVERPRODUKSI MnSOD Staphylococcus equorum REKOMBINAN MENGGUNAKAN PLASMID pCAD_sod DENGAN PROMOTOR AUTOINDUKSI DI Escherichia coli PADA DUA MEDIA SERTA UJI AKTIVITASNYA - Rahma Olga Karya, Anindya
Superoxide dismutase (SOD) is an antioxidant protein which changes superoxide degradation into oxygen and hydrogen peroxide enzymatically. Staphylococcus equorum recombinant MnSOD (rMnSODSeq) overproduction using pJExpress414_sod plasmid in Escherichia coli BL21(DE3) was successfully done in Pharmaceutical Biotechnology Laboratory School of Pharmacy ITB. The expression system utilizes T7 promoter using ð?????????-D-1-thiogalactopyranoside (IPTG) as inducer. The aim of this research is to optimize rMnSODSeq overproduction by using pCAD_sod plasmid with dps autoinduction promoter in E. coli TOP10 using Luria Bertani (LB) and Terrific Broth (TB) media. E. coli carrying pCAD_sod was cultured in 50 mL liquid LB media and the sample were taken at various incubation time. The best incubation time was used for overproduction in 200 mL scale of TB and LB media. rMnSODSeq was purified with nickel column. Activity of rMnSODSeq was observed by zymography and the total amount as well as purity of rMnSODSeq were determined by SDS-PAGE using coomassie blue staining and ImageJ software. Plasmid stability was determined using plasmid retention assay. Cell pellet produced during rMnSODSeq overproduction in TB and LB media for 24 hours respectively were 2.55±0.06 g and 1.52±0.14 g and total amount of rMnSODSeq respectively were 18.90±0.29 mg (30.133%) and 8.48±1.44 mg (48.70%) per 200 mL of E. coli culture. Percentage of purified rMnSODSeq using TB and LB media respectively were 50.66±1.34% and 61.8±0.97% (100% electrophoretic purity) and also respectively were 55.13% and 49.33% (90-99% electrophoretic purity). This result is categorized as good for protein production using E. coli. rMnSODSeq from both media showed dismutation activity. Stability of pCAD_sod plasmid in overproduction condition using LB and TB media is 99.8±0.21% and 100±0%, respectively. Optimum condition for overproduction of rMnSODSeq using pCAD_sod in both media was revealed in this study, which is 37°C, 150 rpm for 24 hours. Results of this research give prospect for using pCAD plasmid for rMnSODSeq production in larger scale.